Digital life together : the challenge of technology for Christian schools - Smith, David, 1966-; Sevensma, Kara; Terpstra, Marjorie; McMullen, Steven (Grand Rapids, MI. William B Eerdmans Publishing Company, 2020)
Digital technologies loom large in the experience of today's students. However, parents, teachers, and school leaders have only started to take stock of the ramifications for teaching, learning, and faith. Based on a three-year in-depth study of Christian schools, Digital Life Together walks educators, school leaders, and parents through some of the big ideas that are hidden in our technology habits, going beyond general arguments for or against digital devices to address the nuanced realities of Christian education in a twenty-first-century context
Context -- Mission -- Teaching and learning -- Discernment -- Formation -- Community
Includes bibliographical references and index
Keywords: Educational technology; Technology -- Religious aspects -- Christianity; Church schools